PERAN PONDOK PESANTREN TERHADAP PENDIDIKAN KARAKTER - Moh Abdullah (Ulumuna: Jurnal Studi Keilsman, 2019)
Absolute education (character) is the basis of every human being that must be internalized in every soul as a human soul, it is a measure of whether someone is good or not. One institution that plays an important role in ahlak education is pondok pesantren. Emphasis in boarding school education is an effort to form a noble man with good personality, good behavior and virtuous, so that attitudes or morals in the world of boarding school education occupy an important position and become the ultimate goal of an education, namely giving birth to people with morals in addition to science. Therefore, moral position is very important for the world of pesantren education. Pondok pesanntren not only conveys material through classic books, but rather to practice in everyday life, so that character education is easily embedded into the souls of students as objects in character education in a boarding school environment. Until now, education is one of the basic education that has been maintained, not displaced by anything, despite continuing trials and panic from various sectors. So that Islamic boarding school educational institutions continue to get good responses from the community. This journal tries to reveal the vital role of pesantren in professional education. Trying to reveal the involvement of Islamic boarding schools in the process of planting ahlak education from the beginning until now.